Gambaran Pemanfaatan Buku Kesehatan Ibu dan Anak (KIA) Oleh Ibu Hamil - Sri Subiyatun (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
This study aims to find out the description of the utilization of KIA book by pregnant women at Sleman Public Health Center, Yogyakarta. The design of this research is descriptive quantitative. By purposive sampling technique, the sample obtained as many as 60 respondents. This study uses questionnaires as a measuring tool and data analysis using univariat. The description of the utilization of KIA book by pregnant women at Sleman Public Health Center, from the use of 60 respondents (100%), utilization of health information as much as 60 respondents (100%). Utilization of KIA book by pregnant women at Sleman Health Center from the use and utilization of health information was 100% positive.